Heart of Stone - Yerimah, Amed P. (Amed Parker), 1957- (Drama (Ibadan, Nigeria), 2015)
Musa runs from death but not far enough from its canny sting. His heart of stone is so cold that his suicide mission radar stringently points at a large gathering of his family and friends. Kaka Patu his grandmother and Amina his fiancee are unavoidably absent but Kaka Vero and Gladys are unlucky. Musa is apprehended and his death becomes inevitable, either subtle or hard. Yerima brings this ugly social reality to stage in Heart of Stone to unveil the depth of man's heart of darkness and the visceral vicissitudes of scripture misinterpretation and misappropriation.